Penegakan Hukum Pidana Terhadap Pelaku Penambangan Pasir Secara Ilegal - Dwi Oktafia Ariyanti; Muhammad Ramadhan; JS Murdomo (Jambura Law Review, 2020)
Mining activities has grown very much, a given result is very given an advantage for the miners. Nevertheless, activities which promise this also also bring an adverse impact on man and the environment when this activity was undertaken not based on the regulation that has been set. Mining illegally also occurred at the sandbanks Parangtritis, sandbanks I know about the Parangtritis are unique and useful for maintained because it is being very specific with the form of a crescent or bacon and is the one and only sandbanks found in the southeast Asia. Arrangement about mining activities that environmentally sound has set out in various regulation, but this appears to have not run as expected, so may is still needed law enforcement tighter and clear to mining sand conducted an illegal. The research was conducted by juridical normative is the approach that was undertaken based on material law by means of reviewing the theory, the concept, a normative law and the regulatory legislation that deals with this research. This approach is known the approach literature, namely by studying books, regulation and other documents related to this research. Criminal law enforcement of the mining sand illegally in sandbanks Parangtritis has started to walk but not yet optimal .The laws governing about mining sand has been is in a few rules, but the law enforcement not is the responsibility of law enforcement officials just, law enforcement is also a responsibility community in an effort to ahead and recover crimes sand mining illegally. Obstacles faced by law enforcement in dealing with crimes sand mining illegal in sandbanks Parangtritis are the lack of legal awareness to the community, economic factors, the lack of knowledge of the community towards the impact of mining sand illegally and factors law enforcement. Key word: Criminal law; Sand Mining; Illegal